Respuesta :

Answer:

Ok:

Step-by-step explanation:

So f°g . means f(g(x)). (The ° should be more center and bigger but I don't know to do that on a keyboard). f(g(x)) means that you replace the x in f(x) with the g(x) function. i.e:

if f(x) = 2x+2

and g(x) = [tex]x^2[/tex]

f(g(x)) = [tex]2x^2+2[/tex].

Similarly, in this case, we get f(x) = 2x-3 and g(x) = 3x-2.

Then, f(g(x)) or f°g(x) is 2(3x-2) - 3.

And we plug in -2 to solve:

2(3(-2)-2)-3.

and get -19.

Check if I am wrong because everyone makes mistakes but that is the way to solve this.

Otras preguntas

ACCESS MORE